Design and Magnetically Analysis of Circular Flux Linear Actuator - Fenercioğlu, A. (Elektronika ir Elektrotechnika, 2010)
In this study design of the circular flux linear actuator (CFLA), three dimensional FEM analysis and analytical approach have been examined. The actuator designed has active translator and passive stator. The number of phase is 3 and there are 6 translator poles. The movement is achieved by 4 pairs of stator poles placed between the corresponding translator poles. The circular translator poles are recommended independently from each other to ensure uniform flux distribution. The weight is lower because there is no joint core and back iron. The maintenance and repair of separate parts are facilitated. Design has been planned as double sided to compensate the forces in the axes other than the movement axis. This provides high force at low inductance with two coils and 4 air gaps in each phase. Stator parts consist of independent double poles. Movement distance can be extended by attaching these poles along the movement axis. The inductance and force parameters of the modeled CFLA have been obtained by simulation works.